1991
DOI: 10.1021/bi00244a019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melittin on molecular dynamics and calcium-ATPase activity in sarcoplasmic reticulum membranes: time-resolved optical anisotropy

Abstract: We have studied the effect of melittin, a basic membrane-binding peptide, on Ca-ATPase activity and on protein and lipid dynamics in skeletal sarcoplasmic reticulum (SR), using time-resolved phosphorescence and fluorescence spectroscopy. Melittin completely inhibits Ca-ATPase activity, with half-maximal inhibition at 9 +/- 1 mol of melittin bound to the membrane per mole of ATPase (0.1 mol of melittin per mole of lipid). The time-resolved phosphorescence anisotropy (TPA) decay of the Ca-ATPase labeled with ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(118 citation statements)
references
References 43 publications
11
106
1
Order By: Relevance
“…For instance, it has been shown that lytic concentrations of melittin dramatically reduce the rotational mobility of band 3 protein in human erythrocyte membranes (Dufton et al 1984;Clague and Cherry 1988;Hui et al 1990) and of bacteriorhodopsin in lipid vesicles (Hu et al 1985). Further, melittin causes aggregation of membrane proteins including band 3 protein (Clague and Cherry 1988), bacteriorhodopsin (Hu et al 1985) and Ca 2+ -ATPase (Voss et al 1991;Mahaney and Thomas 1991;Mahaney et al 1992). In addition, melittin is a potent inhibitor of Ca 2+ -ATPase (Voss et al 1991;Mahaney and Thomas, 1991), H + K + -ATPase (Cuppoletti et al 1989;Cuppoletti, 1990) and Na + K + -ATPase (Cuppoletti and Abbott, 1990).…”
Section: Action Of Melittin On Membrane Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been shown that lytic concentrations of melittin dramatically reduce the rotational mobility of band 3 protein in human erythrocyte membranes (Dufton et al 1984;Clague and Cherry 1988;Hui et al 1990) and of bacteriorhodopsin in lipid vesicles (Hu et al 1985). Further, melittin causes aggregation of membrane proteins including band 3 protein (Clague and Cherry 1988), bacteriorhodopsin (Hu et al 1985) and Ca 2+ -ATPase (Voss et al 1991;Mahaney and Thomas 1991;Mahaney et al 1992). In addition, melittin is a potent inhibitor of Ca 2+ -ATPase (Voss et al 1991;Mahaney and Thomas, 1991), H + K + -ATPase (Cuppoletti et al 1989;Cuppoletti, 1990) and Na + K + -ATPase (Cuppoletti and Abbott, 1990).…”
Section: Action Of Melittin On Membrane Proteinsmentioning
confidence: 99%
“…Further, melittin causes aggregation of membrane proteins including band 3 protein (Clague and Cherry 1988), bacteriorhodopsin (Hu et al 1985) and Ca 2+ -ATPase (Voss et al 1991;Mahaney and Thomas 1991;Mahaney et al 1992). In addition, melittin is a potent inhibitor of Ca 2+ -ATPase (Voss et al 1991;Mahaney and Thomas, 1991), H + K + -ATPase (Cuppoletti et al 1989;Cuppoletti, 1990) and Na + K + -ATPase (Cuppoletti and Abbott, 1990). The experiments with bacteriorhodopsin suggest that immobilization due to aggregation of membrane proteins is a result of direct melittin-protein interactions rather than an indirect consequence of melittin-lipid interactions (Hu et al 1985).…”
Section: Action Of Melittin On Membrane Proteinsmentioning
confidence: 99%
“…Ca 2ϩ ATPase transports two Ca 2ϩ ions across the SR membrane against a large concentration gradient by hydrolytic coupling with one ATP molecule. Structural studies (Toyoshima et al, 1993;Stokes et al, 1994) suggest that Ca 2ϩ ATPase molecules can exist in monomeric and oligomeric forms with enzymatic activity being regulated by its oligomeric state (Squier et al, 1988;Voss et al, 1991Voss et al, , 1994Kutchai et al, 1994). Large aggregates of enzyme have low or no activity, and dissociated enzyme (possibly dimers) has high activity.…”
Section: ؉mentioning
confidence: 99%
“…However, Murphy's data and our own results show that the Ca 2ϩ -ATPase affinity for free fluorescein is not particularly high, being strongly increased (at least two orders of magnitude) by the addition of halogenated substitutes to the molecule. Many authors have used eosin isothiocyanate (Papp et al, 1987;Munkonge et al, 1988) and erythrosin isothiocyanate (Papp et al, 1987;Birmachu and Thomas, 1990;Voss et al, 1991) rather than FITC, due to their higher affinity and particular fluorescence characteristics, to study rotational movements of the SR Ca 2ϩ -ATPase. These authors concluded that both compounds bind to the same site and react with the same lysyl residue as FITC (Papp et al, 1987;Birmachu and Thomas, 1990).…”
Section: Discussionmentioning
confidence: 99%